DESIGN AND DEVELOPMENT OF AIR MONITORING AND QUALITY CONTROL DEVICE USING ARDUINO UNO - Sudiardana, I wayan; ., Widodo (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2019)
LPG (Liquid Petroleum Gas) has been used in everyday life. But if there is leakage it will cause poisoning and explosion. Underlying this, the authors made research on monitoring and control of air quality. The purpose of this study is to make a device that can detect earlier leakage of LPG. This device can detect excess levels of carbon monoxide in the air. Even more, it can avoid the danger of fire and poisoning. The research method used descriptive analysis method and quantitative analysis method. Measurements and testing with accurate reference measuring instruments. Based on testing and analysis, the device can work well with an average percentage error of 1.92% for CO gasmeasurement and 3.1% for LPG gas measurement. Increasing gas content in each sensor is proportional of increasing in the sensor output voltage. Some of the factors that cause errors were the differences of sensor sensitivity and environmental conditions where the sample measured.